2022
DOI: 10.3389/fpsyt.2022.902558
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and symptoms of post-traumatic stress disorder in nurses: A moderated mediation model of maladaptive cognitive emotional regulation and psychological capital

Abstract: Nurses often face a variety of work-related and life-related stresses that make them more prone to symptoms of post-traumatic stress disorder (PTSD), yet the underlying mechanism of this association is poorly understood. To address this research gap, we investigated the mediating role of maladaptive cognitive emotion regulation strategies in the relationship between perceived stress and PTSD symptoms, and explored whether psychological capital could moderate the direct or indirect effects between perceived str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…The results of this study indicate that junior nurses who perceive stress are likely to belong to the low psychological capital category. Although every nurse faces a variety of stressors in their work scenario, the impact of these stressful events depends in part on how the individual perceives the stress generated by these events to be ( 46 , 47 ). Junior nurses with low psychological capital are accustomed to characterizing stressful events with negative perceptions, thus perceiving more stress and being affected by it ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicate that junior nurses who perceive stress are likely to belong to the low psychological capital category. Although every nurse faces a variety of stressors in their work scenario, the impact of these stressful events depends in part on how the individual perceives the stress generated by these events to be ( 46 , 47 ). Junior nurses with low psychological capital are accustomed to characterizing stressful events with negative perceptions, thus perceiving more stress and being affected by it ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…PsyCap has correlated negatively with many RNs' undesired work-related outcomes. It correlated negatively with burnout in 12 studies Bae et al, 2021;Bao & Taliaferro, 2015;Flinkman et al, 2023;Kim & Kweon, 2020;Li et al, 2019;Liu et al, 2021;Peng et al, 2013;Tang et al, 2023;Yıldırım et al, 2021;Zhou, Yang, et al, 2018;Zhu, Shen, et al, 2021), with stress in five studies (Hao et al, 2020;Kim & Kweon, 2020;Liu et al, 2021;Xue et al, 2022;Yim et al, 2017) and with psychological distress in three studies (Brunetto, Rodwell, et al, 2016;Xiao et al, 2022;Zhou et al, 2017). health and well-being has been highlighted as an important component in retaining the healthcare workforce (Anderson et al, 2021).…”
Section: Outcomes Of Psycapmentioning
confidence: 99%
“…Previous studies have shown that cognitive reappraisal can relieve individuals' negative emotions caused by stress [38,39]. Under the pressure of pregnancy, maternal with high cognitive reappraisal may be more able to adapt and eliminate the adverse effects of stress on negative outcomes.…”
Section: The Moderating Role Of Cognitive Reappraisalmentioning
confidence: 99%